Analysis of The Effectiveness Combination Allium Ascalonicum L. And Zingiber Officinale Var. Rubrum Extracts On Uric Acid Levels In Hyperuricemic Rattus Norvegicus - Marwan, Deinike Wanita; Irenesia, Bimby; Eryta, Evy; Sartika, Wiwi; Aflah, Randhy (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2025)
BackgroundHyperuricemia is an increase in uric acid levels caused by increased uric acid metabolism (overproduction), decreased uric acid excretion through urine (underexcretion), or a combination of both. In Indonesia, the average age of occurrence is younger compared to Western countries, with approximately 32% of hyperuricemia cases occurring under the age of 34. The long-term and excessive use of medication can lead to toxic side effects. Previous studies have indicated that certain plants have effects in lowering uric acid levels, such as shallots (Allium ascalonicum L.) and red ginger (Zingiber officinale var. rubrum). Objective :To analyze the effectiveness of the combined extract of Allium ascalonicum L. and Zingiber officinale var. rubrum in reducing uric acid levels in male white rats induced with potassium oxonate. Method : An experimental study using a Pre-Post Test Control Group Design with a combination of shallot and red ginger extracts. The samples were divided into five groups. Result : Based on the One-Way ANOVA test conducted before and after the treatment, a p-value of <0.05 was obtained, indicating that the combination of shallot and red ginger extracts was effective in reducing uric acid levels in hyperuricemic rats. The combination of 450 mg red ginger extract and 150 mg shallot extract showed the most effective and significant reduction in uric acid levels. Conclusion : The combination of shallot and red ginger extracts is effective in reducing uric acid levels in hyperuricemic rats. Keywords : hyperuricemia, red ginger, shallots, uric acid levels